The Wild West of Eastern Europe A Ukrainian Guide on Breaking Free from Empire - Kazarin, Pavlo 1983- (ibidem, 2024)
Ukraine is the new West Berlin of Eastern Europe. The annexation of Crimea and the Russian invasion of the Donets Basin (Donbas) forced the Ukrainian nation to change. In 2013, it was still a post-Soviet country with a divided identity. Today, it is an outpost of Europe which has been holding back the onslaught of the Russian army for several years now. The Wild West of Eastern Europe by Pavlo Kazarin is a book about how such a transformation has become possible. In 2022, the Ukrainian version of this volume was named "Book of the Year" by BBC Ukraine in the category of "Essay Writing"
Keywords: Ukraine; History